Laparoscopic rectal resection—the road to safety surgery - Milone, Marco; Manigrasso, Michele; Burati, Morena (Annals of Laparoscopic and Endoscopic Surgery, 2017)
Total mesorectal excision (TME) indicates a surgical technique for the removal of the rectum and mesorectum during an anterior resection for rectal cancer. The concept of complete TME was first described by Heald in 1979. In the past ten years laparoscopic total mesorectal excision (LTME) has been introduced as an alternative to the open technique and proved to be equivalent by many studies. Anyhow, the laparoscopic approach is technically more challenging than the open one, and its learning curve is often longer. The purpose of this study is to suggest a standardization of the procedure by suggesting a critical view of safety for laparoscopic rectal resection, advising some tips and tricks which could benefit its learning and its performance.